Particular features of angiogenesis in lesions in patients suffering from basal cell epithelioma - A. N. Khlebnikova; N. V. Novoselova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Basal cell epithelioma is one of the most frequent malignant skin neoplasms. Angiogenesis plays an important part in the development of basal cell epithelioma. The article presents a review of the angiogenesis of this tumor with the help the immunohistochemistry analysis using CD31 and CD34 markers. The authors established a reliable relationship between the number of vessels expressing CD31 and those expressing CD34 in the superficial and nodular forms of the tumor as well as superficial, multi-center, nodular and infiltrative basal cell epitheliomas. A comparison of the number of vessels expressing CD31 and CD34 markers in different histological types made revealed a trend to their growth in the infiltrative type vs. superficial, multi-center and nodular ones.